Electronic commerce for a computer shop - Tan, Yaw Ten (2003)
The Electronic Commerce DH Computer (ECDH) is a system that uses the concept of business-to-consumer transaction, transaction processing systems and management information systems. The main objectives are to improve cost effectiveness, support the implementation of business functions, provide value added service and improve relationships with customers. The system is developed using the System Development Life Cycle (SDLC) methodology. The system is developed using ASP 3.0; Microsoft Access 2000 as database and Microsoft Windows 2000 Advanced Server as operating system. The system is a web-based application, which facilitates users in online enquiries on product catalogue, shopping cart, customer support services and make the online purchase order. The system also provides maintenance of customer records and supplier profile. The user satisfaction evaluation on the system shows favorable result though some shortcomings have to be overcome. Recommendations suggested in this study can be implemented in order to further enhance the system.